Evaluating ELISA, Immunofluorescence, and Lateral Flow Assay for SARS-CoV-2 Serologic Assays - Michel, Moïse; Bouam, Amar; Edouard, Sophie; Fenollar, Florence; Di Pinto, Fabrizio; Mège, Jean-Louis; Drancourt, Michel; Vitte, Joana (Frontiers in Microbiology, 2020)
Background. The SARS-CoV-2 outbreak has emerged at the end of 2019. Aside from the detection of viral genome with specific RT-PCR, there is a growing need for reliable determination of the serological status. We aimed at evaluating five SARS-CoV-2 serology assays. Methods. An in-house immunofluorescence assay (IFA), two ELISA kits (EUROIMMUN® ELISA SARS-CoV-2 IgG & NovaLisa® SARS-CoV-2 IgG and IgM) and two lateral flow assays (T-Tek® SARS-CoV-2 IgG/IgM Antibody Test Kit & Sure Bio-tech® SARS-CoV-2 IgM/IgG Antibody Rapid Test) were compared on 40 serums from RT-PCR-confirmed SARS-CoV-2 infected patients and 10 SARS-CoV-2 RT-PCR negative subjects as controls. Results. Control subjects tested negative for SARS-CoV-2 antibodies with all five systems. Estimated sensitivities varied from 35.5 % to 71.0 % for IgG detection and from 19.4 % to 64.5 % for IgM detection. For IgG, in-house IFA, EuroImmun, T-Tek and NovaLisa displayed 50 % to 72.5 % agreement with other systems except IFA vs EuroImmun and T-Tek vs NovaLisa. Intermethod agreement for IgM determination was between 30 % and 72.5 %. Discussion. The overall intermethod agreement was moderate. This inconsistency could be explained by the diversity of assay methods, antigens used and immunoglobulin isotype tested. Estimated sensitivities were low, highlighting the limited value of antibody detection in CoVID-19. Conclusion. Comparison of five systems for SARS-CoV-2 IgG and IgM antibodies showed limited sensitivity and overall concordance. The place and indications of serological status assessment with currently available tools in the CoVID-19 pandemic need further evaluations.